"Acute" asthma in adults. Issue 1 (February 1979) - Bellamy, D; Collins, J V
Abstract : Forty-four adult patients with acute severe asthma were studied on admission to a general hospital to determine the mode of presentation and clinical severity of the acute illness. Most patients described poorly controlled wheezing for a mean period of five weeks before a more rapid deterioration, usually over 24 hours, caused them to seek medical attention. The clinical severity of the acute attach was not related to the duration of acute wheezing before admission to hospital. Recovery, studied in 11 of the patients, was slow, and most had reached only 70% of their predicted spirometric values after seven days' treatment in hospital. The rate of recovery was not influenced by the antecedent history of acute wheezing. Very sudden deterioration from a background of good control appears to be uncommon in adults with asthma who present to hospital as emergencies, and it is likely that improvement in the standard of routine management of asthmatics at home would prevent many such admissions.